2013
DOI: 10.4209/aaqr.2012.08.0232
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Contribution of Wildfires to Ozone Concentrations in the Central US-Mexico Border Region

Abstract: The annual trends and spatiotemporal patterns of monthly 8-hour maximum ozone (8-hr max O 3 ) concentrations in the Paso del Norte region were analyzed, and their associations with fires were examined for the 2001-2010 period. Hourly O 3 measurements were retrieved from the Environmental Protection Agency (EPA) Air Quality System, while the times and locations of fires were acquired from the MODIS fire detection module. The absolute 8-hr max O 3 concentrations were comparable in urban, rural and background sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…We previously determined that biomass burning contributed 3.0 μg/m 3 to PM 2.5 ; however, the profiles of the remaining factors also contained elemental and organic carbon (Chalbot et al, 2013a,b,c,d). The outcomes of the PMF analysis were re-processed by regressing the factor contributions to organic carbon (OC) and elemental carbon (EC) levels to estimate the influence of biomass burning on PM 2.5 OC and EC.…”
Section: Resultsmentioning
confidence: 99%
“…We previously determined that biomass burning contributed 3.0 μg/m 3 to PM 2.5 ; however, the profiles of the remaining factors also contained elemental and organic carbon (Chalbot et al, 2013a,b,c,d). The outcomes of the PMF analysis were re-processed by regressing the factor contributions to organic carbon (OC) and elemental carbon (EC) levels to estimate the influence of biomass burning on PM 2.5 OC and EC.…”
Section: Resultsmentioning
confidence: 99%
“…At HPO and MBO, which are both strongly influenced by springtime outflow from East Asia, the O 3 levels showed larger increases at higher percentile levels than those at lower percentile levels (Gratz et al 2015;Tanimoto 2009). A statistically significant positive trend in the mean maximum daily 8-h average (MDA8) O 3 concentration at 0.12 ppb year −1 was observed at CHA for the period from 1989 to 2010 (Chalbot et al 2013). The surface O 3 recorded at MLO in the Northern Pacific has shown a significant increase of 0.16 ± 0.04 ppb decade −1 (Oltmans et al 2013).…”
Section: Seasonal Variationsmentioning
confidence: 90%
“…Jaffe et al (2008) showed that the area of summer burning in the western USA was significantly correlated with daytime summer O 3 concentrations at LAV and YEL, which indicates that the presence of fire played an important role in increasing the summer O 3 in the western USA. Chalbot et al (2013) indicated that regional fire incidents might trigger high O 3 episodes. They estimated a 3 ppb increase in the MDA8 O 3 concentration at CHA in Arizona by such incidents within 400 km of the sites.…”
Section: Biomass Burningmentioning
confidence: 99%
“…These plumes can also affect nearby cities leading to ground level concentrations that largely surpass air quality standards [8,10,11]. Nevertheless, there are few evaluations regarding ozone behavior in large cities exposed to polluted masses transported from nearby forest fires [3,8,11,12] Results range from moderate decreases at Arizona and Central Texas, US, and western Mexico, when the cities are located less than 400 km from fire [12], to large increases as in the city of Edmonton, Canada, when the city is located 300 km from the fire [11]. On the other hand, measurements in Mexico City (MCMA) did not demonstrate significant differences in ground level ozone concentrations in periods with active fires [13].…”
Section: Introductionmentioning
confidence: 99%